SEMIOTIKA BATIK PERANAKAN DI PEKALONGAN - Andri Nur Cahyo; Yustiana Dwirainaningsih; Amin Sulistyowati (Canthing, 2022)
Peranakan batik is the term for batiks produced by Indonesians of Chinese descent. The presence of Peranakan batik has contributed to the diversity and enriching of the Indonesian Batik repertoire. One of the centers producing Peranakan batik is Pekalongan. Peranakan batik in Pekalongan has its own uniqueness compared to other coastal batik. This uniqueness can be seen in the visualization of the motifs and the socio-cultural conditions of Pekalongan. This article examines the phenomenon of Peranakan batik in Pekalongan in terms of its visualization and aesthetic meaning. The approach used is Roland Barthes' semiotic theory. The focus of the reading is on three batik craftsmen of Chinese descent in Pekalongan, namely Oey Soe Tjoen, Ozzy, and Bulan. It is hoped that this article can provide information about the aesthetic elements of Peranakan batik in Pekalongan, as well as invite the public to better appreciate cultural diversity and the role of acculturation in the development of batik in Pekalongan. Keyword: Acculturation, Peranakan Batik, Pekalongan, Semiotic.